Investigating Stress Transfer Between the Tuz Gölü Fault Zone and Hasan Dağ Volcano (Turkey) - Hedger , Emily; Gottsmann , Jo (Frontiers in Earth Science, 2022)
Faulting, magmatism and volcanism are intrinsically linked by plate tectonics. Fault slip imparts stress changes to the surrounding crust and other faults and fractures. Volcano-tectonic hazard assessment in areas with long recurrence intervals of volcanic and tectonic activity requires an assessment of current stress levels. Here we investigate stress transfer between the Akhisar-Kiliç fault segment (AKFS) of the seismically active Tuz Gölü fault zone in the Central Anatolian Volcanic Province and the active Hasan Dağ volcanic complex. Current stress accumulation by protracted gradual slip on the AKFS since its most recent rupture (5.45 ka±0.16 BP) is quantified using the Coulomb Failure Stress change (ΔCFS). We calculate currently accrued ΔCFS magnitudes of between 2.5±0.2 and 15±0.5 MPa on the fault plane for published lower and upper-bound estimates of right-lateral slip rates, respectively. These changes are sufficient to promote failure of the segment. The M5.1 September 20, 2020 earthquake SW of Hasan Dağ occurred in a volume predicted by this study to have undergone fault unclamping by gradual slip along the AKFS. We also show that gradual slip of the AKFS contributes to the progressive unclamping of fractures and transtensional opening of potential magma pathways oriented perpendicularly to the AKFS both above and below Hasan Dağ’s magma reservoir, while pathways oriented parallel to the AKFS are being clamped. Earthquake moment magnitudes of between Mw5.94 and Mw6.76 due to hypothetical partial or complete rupture of the segment exacerbate these trends. The spatial pattern of Coulomb failure stress changes on Hasan Dağ’s magma reservoir is predominantly controlled by the location of rupture relative to the reservoir with the magnitude of the earthquake playing a subordinate role. We explore implications of our findings for the assessment of interconnected seismo-volcanic hazards and associated risks.